1994
DOI: 10.1111/j.1528-1157.1994.tb02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin (Neurontin) as Add‐on Therapy in Patients with Partial Seizures: A Double‐Blind, Placebo‐Controlled Study

Abstract: A multicenter, double-blind, randomized, placebo-controlled study evaluated the efficacy and safety of gabapentin (Neurontin, GBP) as add-on therapy in 272 patients with refractory partial seizures who were receiving one to two standard antiepileptic drugs (AEDs). Efficacy assessments compared the frequency of partial seizures during the 12-week treatment phase (T) and the 12-week baseline period (B). The primary analysis compared data for patients receiving GBP 900 mg/day with placebo; the GBP 1,200-mg/day gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(90 citation statements)
references
References 17 publications
5
78
1
3
Order By: Relevance
“…Consistent with the safety profile of gabapentin shown in the previous study, [4][5][6] the most common adverse events were somnolence (44-51%) and dizziness (19-20%). Of note, placebo patients receiving other AED, also reported somnolence (20.7%) and dizziness (4.9%).…”
Section: Safety/tolerabilitysupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with the safety profile of gabapentin shown in the previous study, [4][5][6] the most common adverse events were somnolence (44-51%) and dizziness (19-20%). Of note, placebo patients receiving other AED, also reported somnolence (20.7%) and dizziness (4.9%).…”
Section: Safety/tolerabilitysupporting
confidence: 72%
“…Each has demonstrated a statistically significant decrease in seizure frequency for gabapentin patients compared to placebo patients. [4][5][6] In addition, there was a 25% overall gabapentin responder rate, defined as the percentage of patients with ≥50% decrease in seizure frequency. 7 A phase II Japanese trial for gabapentin demonstrated a responder rate of approximately 22-24% when used as an adjunctive therapy in patients with refractory epilepsy receiving no more than three existing AED.…”
Section: Introductionmentioning
confidence: 99%
“…The ethics committee at each center approved the protocol, and a written statement of informed consent was obtained before study entry. The study consisted of a screening visit, then an 8-week baseline, followed by a 24-week treatment period, with evaluations at the start and end of the baseline phase, and after 2,4,8,12,16,20, and 24 weeks of treatment. Patients were aged 12 years or older at study entry and were experiencing more than two partial-onset seizures per month with or without secondary generalization despite therapy with one to three concurrent antiepileptic drugs (AEDs).…”
Section: Methodsmentioning
confidence: 99%
“…Quality of life was assessed by administering the QOLIE-10 questionnaire at screening, at week 16 of treatment, and at the final visit. Patients were assessed at screening and at weeks 0, 2,4,8,12,16,20, and 24 of the treatment phase. Responders were defined as those patients who recorded a ജ50% reduction in seizure frequency compared with the baseline phase.…”
Section: Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation